Trade and Innovation in the Korean Information and Communication Technology Sector - Onodera, Osamu (OECD Publishing, 2009)
This case study analyses the effect of trade and investment liberalisation on Korea's information and communication technology (ICT) sector and finds that trade and investment have played a crucial role in innovation in this sector. In the initial stages of development, imported capital goods and components, joint ventures, licensing and Original Equipment Manufacturer (OEM) contracts were important sources of technology and exports were key to obtain the necessary economies of scale for innovation. Free trade and investment policies in the 1990s and stronger protection of intellectual property rights have led to an increase in R&D and innovation, which in turn has led to the transformation of Korea into a knowledge-based economy. Keywords: innovation, Korea, information and communication technology, ICT, trade reform, Samsung, production network, intellectual property rights, IPR protection, patents, ITA, Information Technology Agreement